2022
DOI: 10.1186/s12913-022-07923-5
|View full text |Cite
|
Sign up to set email alerts
|

Organizational readiness to implement the Serious Illness Care Program in hospital settings in Sweden

Abstract: Background The Serious Illness Care Program (SICP) is a model developed for structured communication, identifying patients, and training physicians to use a structured guide for conversations with patients and family members. However, there is a lack of knowledge regarding the sustainable implementation of this conversation model. Therefore, the aim of this study was to identify barriers and enablers during the implementation of the SICP in hospital settings. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…For instance, having SIC can interfere with beliefs that the physician’s professional role is to “treat”, not to talk about values and goals [ 16 ]. Physicians’ attitudes and their own capabilities in SIC have been described as both an enabler and a barrier [ 17 ]. However, altering mindsets and creating culture shifts regarding attitudes and norms around SIC can occur alongside the implementation process [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, having SIC can interfere with beliefs that the physician’s professional role is to “treat”, not to talk about values and goals [ 16 ]. Physicians’ attitudes and their own capabilities in SIC have been described as both an enabler and a barrier [ 17 ]. However, altering mindsets and creating culture shifts regarding attitudes and norms around SIC can occur alongside the implementation process [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physicians’ confidence in their ability to find time to conduct ACP conversations remained low, and constitutes an organizational barrier, as described by Andersson and Sandgren in their recent study of organizational readiness to change. 20 The high level of burnout among physicians in hemato-oncology calls for institutional interventions in addition to training. A work organization allocating time to conduct goals of care conversations could be one the means.…”
Section: Discussionmentioning
confidence: 99%
“…15 16 A study describing organisational factors related to implementing the SICP found that clinicians' confidence, motivation and attitudes to enacting serious illness conversations could act as barriers as well as facilitators to the implementation. 17…”
Section: Introductionmentioning
confidence: 99%